Effect of gestational anemia on breastfeeding- a prospective follow-up -study - Kemppinen, Lotta; Mattila, Mirjami; Ekholm, Eeva; Perasto, Laura; Karlsson, Hasse; Mäkikallio, Kaarin; Karlsson, Linnea (BMC, 2025)
Background
Gestational anemia is a common pregnancy complication that affects approximately 40% of pregnant women globally. The health benefits of breastfeeding are widely acknowledged for both mothers and infants, and recognizing the factors that affect the duration and quality (exclusive / partial) of breastfeeding is therefore of great importance.
Methods
Women who participated in the FinnBrain Birth Cohort during 2011–2015 and whose hemoglobin levels were available in the third trimester (n = 1238) were included in this prospective study. The study group comprised women in the third trimester with an Hb < 110 g/l (n = 150), while women with an Hb ≥ 110 g/l served as the control group (n = 1088). The duration of breastfeeding was recorded as a categorical variable in line with the Finnish breastfeeding guidelines, which specify 4 months as the cut-off for exclusive breastfeeding, and as a continuous variable for exclusive and partial breastfeeding. Maternal and neonatal data were collected from the Medical Birth Register and self-reports. The data were adjusted for maternal education, parity, mode of delivery, and maternal depression.
Results
The median (range) duration of exclusive breastfeeding was 4 (0–6) months in the study group and 4 (0–10) months in the control group (p =.461). Among the women in the study group, 60% reached the recommended goal of exclusive breastfeeding of 4 months, while the proportion was 66% among the women in the control group (p =.185). The duration of exclusive breastfeeding was shorter among the women who suffered from depressive symptoms (Edinburgh Postnatal Depression Scale (EPDS) ≥ 12) three months postpartum. The duration of partial breastfeeding was 7 and 8 months in the study and control groups, respectively (p =.080).
Conclusions
In our prospective study cohort, gestational anemia in the third trimester did not associate with the duration and quality of breastfeeding after adjusting for confounding factors.